Uterine inertia in a rabbit doe - ISLAM, RAFIQUL; SARKAR, T K; NADROO, G A; GANAI, T A S (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia due to uterine inertia in rabbit doe was treated with combined oral and parenteral calcium therapy along with parenteral injection of Oxytocin and delivered all the live kits successfully.